TRANSPARANSI DALAM PROSES SELEKSI CALON ANGGOTA PANITIA PENGAWAS (PANWAS) PEMILU TAHUN 2017: STUDI KASUS DI KABUPATEN BENGKALIS, KABUPATEN ROKAN HILIR, KOTA DUMAI, DAN KOTA PEKANBARU - nasution, sri roserdevi; harsini, harsini; kusumawardhani, fajarwaty (FAKULTAS ILMU ADMINISTRASI UNIVERSITAS LANCANG KUNING, 2018)
This study aims to determine and analyze the selection process of candidate members of the Election Supervisory Committee (Panwas) Election in two districts and two cities in the province of Riau. The selection takes place in mid-2017, in response to Law No. 15 of 2011 on General Election. Moreover, Riau will hold the Elections to the Regions in 2018 and Legislative Election and the Presidential and Vice Presidential Election in 2019. The existence of Panwas is a necessity in the effort to make the election more qualified and produce leaders in accordance with the conscience of the people. But please note how transparency in the selection process of candidates for Panwas members who have a very big mandate in the nation's democratic process. Selection of Panwas member candidates should fulfill the element of transparency as a proof of the implementation of good governance.The method used in this research is qualitative research methods. Data collection is done by using primary data in the form of in-depth interviews to the informants.Purposive sampling is chosen to be a technique in getting informants in accordance with this research. In addition, secondary data derived from the Election Supervisory Agency and mass media documents also support and sharpen the case studies as the analytical blades in this study.